Religious Nationalism and the Seek for Ontological Assurance - Aliyev, Bahlul (CenRaPS Journal of Social Sciences, 2020)
Religious nationalism is a phenomenon that has been discussed a lot after the Iranian revolution and is still present today. The ever-changing global events and political trends keep this phenomenon dynamic. In particular, despite the triumphant perception of globalization, some social scientists believe that this phenomenon will also fail, based on the reactivity of societies, and try to explain the reactivity of society with the principle of marginalization of religions. Although this study is essentially a literature review that compiles the ideas and discourses of scientists who have contributed significantly to the subject within the discipline of Sociology of Religion, it also aims to examine how religious nationalism and the search for ontological assurance affect this phenomenon as the factor affecting the phenomenon of marginalization. Learning the role of these phenomena in the resistance of society to innovative events constitutes the aim of the study.